1967
DOI: 10.1111/j.1365-2621.1967.tb09705.x
|View full text |Cite
|
Sign up to set email alerts
|

Pea Lipoxidase, Distribution of Enzyme and Substrate in Green Peas

Abstract: SUMMARY— The activity of the enzyme lipoxidase and the concentrations of free and lipid‐bound fatty acids in different parts of green peas were determined. The extractable enzyme was found mainly in the cotyledon, where its concentration was also highest. The concentration of the enzyme was somewhat higher in the inner than in the outer part of the cotyledon. Both free and bound fatty acids were found in all parts of the pea. The oxidation rate of linoleic acid, catalyzed by lipoxidase, was found independent o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1970
1970
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 19 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…Alcohols are present in plants likely formed through physical damage, during storage, and processing (Eriksson, 1967;Goncalves et al, 2016). The alcohols identified in nkui constituted a total of 4% ( Figure 2).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Alcohols are present in plants likely formed through physical damage, during storage, and processing (Eriksson, 1967;Goncalves et al, 2016). The alcohols identified in nkui constituted a total of 4% ( Figure 2).…”
Section: Re Sults and Discussionmentioning
confidence: 99%
“…Absence or very small amounts of free fatty acids has been reported in fresh peas, however, during storage or freezing, their concentration increases due to enzymatic action (Eriksson, 1967). Alcohols can also be produced due to physical damage or subsequent processing of plant materials (De Lumen et al, 1978).…”
Section: Alcoholsmentioning
confidence: 98%
“…Lipoxidase is an enzyme present in peas, (Eriksson, 1967) which catalyzes the oxidation of unsaturated fatty acids, mainly linoleic acid in the presence of molecular oxygen. Hexanal and pentanal have been reported as the lipoxidase catalyzed oxidation products of unsaturated fatty acids (Barra et al, 2007;Oomah & Liang, 2007;Whitfield & Shipton, 1966) and are commonly identified in fruits and vegetables (Oomah & Liang, 2007).…”
Section: Aldehydesmentioning
confidence: 99%
“…Physical damage, storage and processing of seeds could lead to the formation of alcohols (Eriksson, 1967;de Lumen et al, 1978;Oomah & Liang, 2007). Volatile alcoholic compounds have distinct characteristics and they could therefore affect the taste and flavour of peas.…”
Section: Alcoholsmentioning
confidence: 99%